Strategi Pemasaran Produk Olahan Sagu DD (Studi Kasus : CV. Breaven Pulau Ambon) - Salasa, Sonia; Timisela, Natelda R; Kembauw, Esther (Universitas Pattimura, 2024)
The research aims to determine strengths and weaknesses (internal factors) and opportunities and threats (external factors) for the CV. Breaven company, the research was conducted at the CV. Breaven company located at Jln. Waiyari Dalam RT 40 Negeri Suli, using descriptive and qualitative analysis methods. The analytical tools that support qualitative research are IFAS analysis and EFAS; the results showed that the company is in the position of cell I growth; the combined value of IFAS is 3.70, and the EFAS value is 3.20.